2013
DOI: 10.2807/1560-7917.es2013.18.39.20593
|View full text |Cite
|
Sign up to set email alerts
|

High uptake of HPV immunisation in Scotland – perspectives on maximising uptake

Abstract: In September 2008, Scotland introduced a national human papillomavirus (HPV) immunisation programme with bivalent HPV vaccine, to prevent cervical cancer. This school-based programme routinely vaccinates girls aged between 12 and 13 years. A catch-up campaign, running over three years, also began at this time, offering vaccination to all girls aged 13 years to under 18 years old. The HPV immunisation campaign presented challenges due to this vaccine being targeted to girls in school and older girls who had lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…This is true also for the Swedish national vaccination programme where the uptake is above 80% [ 26 ]. Likewise, recent evaluations of implementation strategies for HPV catch-up vaccination among adolescents in Australia and Scotland has suggested that school-based campaigns are successful in terms of reaching high vaccination coverage [ 20 , 22 , 23 ]. Our study provides evidence that school-based delivery of HPV vaccine to the catch-up group results in high HPV vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This is true also for the Swedish national vaccination programme where the uptake is above 80% [ 26 ]. Likewise, recent evaluations of implementation strategies for HPV catch-up vaccination among adolescents in Australia and Scotland has suggested that school-based campaigns are successful in terms of reaching high vaccination coverage [ 20 , 22 , 23 ]. Our study provides evidence that school-based delivery of HPV vaccine to the catch-up group results in high HPV vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Coverage in the target cohort in Scotland has exceeded 90% for three doses for over 4 years running 16 . The Scottish program was highly organised, taking a project management approach to program implementation, and using existing comprehensive community health data systems and registers, which are supported by a unique identification number for each person 17 . For Australia to achieve higher coverage, a systems‐based approach to identifying and minimising barriers may be required.…”
Section: Discussionmentioning
confidence: 99%
“…37,51,[56][57][58][59][60] A school-based vaccination programme can achieve a vaccination uptake rate of 65.1% to 94.4% for at least 1 dose, as seen in Taiwan, Australia, Canada, Scotland, and Norway. 37,[53][54][55][56]58,60 These studies supported that implementing HPV vaccination through a school-based approach is an effective way of reaching targets directly. Parents are also easily contacted for consent, and schools can be the ideal channel for health promotion and education.…”
Section: Facilitators Of and Barriers To The Uptake Of Hpv Vaccinationmentioning
confidence: 99%